Impact of Service Quality and Service Innovations on Competitive Advantage in Retailing - R. Neni Kusumadewi; Otong Karyono (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Current competitive environment induced by 4.0 industrial revolution has forced companies to focus on managing service to customer by provide added value to customers, so that it will increase competitiveness. This study aims to find out and analyze impact of service quality and service innovations on competitive advantage. Analysis method is descriptive statistical and Structural Equation Modeling with AMOS software. The sampling Technique was purposive sampling with combination cluster proportional stratified random sampling, the instrument to collect the data was questionnaire with manager, supervisor or employee of retailing. The results indicate that the service quality and service innovations impact on competitive advantage.